The Challenges of Conducting a Nurse-Led Intervention in a Randomized Controlled Trial with Vulnerable Participants - Tanya Park; Kim Usher; Kim Foster (Nursing Research and Practice)
This paper discusses the challenges encountered by researchers while conducting a randomized controlled trial (RCT) testing the efficacy of a healthy lifestyle educational and exercise intervention for people with serious mental illness. RCTs, even though considered the “gold standard” of research designs, are still prone to risks of potential bias and threats to their validity. Based on researcher reflexivity, the combination of reflection and action, during the conduct of the study, this paper outlines a number of challenges faced by the researchers. These included managing the need of participants to tell their story and be heard, reluctance of participants to remain in allocated groups, participant literacy, dual role of the nurse nurse-researcher, and reporting the benefits of nonstatistical results of a quantitative research project. Recommendations for conducting future behaviour intervention studies of this type include the incorporation of a reflexive component for the nurse nurse-researcher, highlighting the importance of taking a reflexive stance in both qualitative and quantitative research designs.